2022
DOI: 10.3390/jmse10101454
|View full text |Cite
|
Sign up to set email alerts
|

Ballast Water Dynamic Allocation Optimization for Revolving Floating Cranes Based on a Hybrid Algorithm of Fuzzy-Particle Swarm Optimization with Domain Knowledge

Abstract: Ballast systems and ballast water dynamic allocation between ballast tanks are very important for ensuring the offshore operation efficiency and safety of the revolving floating crane (RFC). Its modeling and solving have multiple difficulties such as modeling complexity, solving complexity and engineering practicability. Early studies showed that domain knowledge is of great significance for the optimization of the design quality and innovation of such complex engineering issues. By analyzing the coupled opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Long [3] introduced an improved genetic algorithm to optimize the allocation of ballast water in barges, with results indicating that the improved genetic algorithm has a shorter computation time and higher efficiency. Liu et al [4] proposed an optimization scheme based on the fuzzy particle swarm optimization algorithm for the ballast-allocation problem, and their comparative results demonstrated the advantages of this method in terms of efficiency improvement, reduced computation time, and good applicability. Topalov et al [5] developed an information system for the real-time acquisition of the operational parameters of the ballast system, and the research results confirmed the effectiveness of this information system for realizing the automatic allocation of ballast water.…”
Section: Crane Ballast Systemmentioning
confidence: 99%
“…Long [3] introduced an improved genetic algorithm to optimize the allocation of ballast water in barges, with results indicating that the improved genetic algorithm has a shorter computation time and higher efficiency. Liu et al [4] proposed an optimization scheme based on the fuzzy particle swarm optimization algorithm for the ballast-allocation problem, and their comparative results demonstrated the advantages of this method in terms of efficiency improvement, reduced computation time, and good applicability. Topalov et al [5] developed an information system for the real-time acquisition of the operational parameters of the ballast system, and the research results confirmed the effectiveness of this information system for realizing the automatic allocation of ballast water.…”
Section: Crane Ballast Systemmentioning
confidence: 99%
“…In the case of high repurchase motivation driven (HRMD) and medium repurchase motivation driven (MRMD) methods, an improved linear time complexity simulated annealing (SA) algorithm was used to solve the NP hard assignment problem. Liu et al [22] proposed a fuzzy particle swarm optimization (FPSO) algorithm, which uses fuzzy logic reasoning to process domain knowledge, improve the solution quality, and obtain the optimal allocation scheme. By comparing with other algorithms, three different examples were provided to demonstrate the effectiveness of the proposed model and algorithm.…”
Section: Related Workmentioning
confidence: 99%